Impression management and non-GAAP disclosure in earnings announcements - Guillamon-Saorin, Encarna (2018)
Funding: FCT-Foundation for Science and Technology in Portugal (grant nr. PTDC/EGE-GES/103770/2008), Spanish Ministry of Science and Innovation (grant nr. SEJ2007-67582-C02-02/ECON, ECO2010-19314), Ministerio de Economia y Competitividad (grant nr. 2014/00452/001), Comunidad Autonoma de Madrid (grant nr. SEJ2008-00059-003) and Nova Forum